A FERRITE POTENTIAL INFLUENCE ON HEAT TRANSFER CONDITIONS IN INDUSTRIAL MOLD DURING THE CONTINUOUS CASTING OF STEELS - Karlinski, V.; Fogazzi, W.; de Souza, B. V.; Ferreira, C. R. F.; dos Santos, C. A.; Spim, J. A. (Revista de Engenharia Térmica, 2009)
This paper aims to apply a solidification mathematical model to the process of the continuous casting of steel. Heat transfer coefficients in the mold were determined by the inverse method and they are related with both macrostructure conditions and carbon equivalents of carbon steels from peritectic reactions. Both structure characterization and ferrite potential were established by solidification parameters and chemical composition after casting. Samples were cut at different positions of the metal/mold interface, whereas the selected sections were polished and etched with a reagent for the metallographic examination. The image processing system was used to analyze as-cast structure for every selected position. It was observed that during casting, numerical predictions about metal/mold heat transfer coefficients along the mold are in accordance with type-A and B steels ferrite potential, due to both its sticking and depression tendency.